2013
DOI: 10.1590/s1516-05722013000300018
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of sage (Salvia officinalis L.) essential oil from the Rio de Janeiro State (Brazil)

Abstract: ABSTRACT:The purpose of this study was to investigate the chemical composition of the essential oil from fresh leaves of sage (Salvia officinalis L.) from Petrópolis, Rio de Janeiro State, for international trade. The oil was isolated by hydrodistillation in a Clevenger-type apparatus and analyzed through a combination of GC-FID and GC-MS. The yield was 2.3 % on dry basis. Forty-seven constituents were identified according to their chromatographic retention indices and mass spectra, corresponding to 94.90 % of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 15 publications
4
16
0
Order By: Relevance
“…Also, studies performed in Brazil [7][25] [55] showed high concentrations of a-thujone, 1,8-cineole, and camphor as the principal components, very similar to the levels we found, although they found no manool or viridiflorol.…”
Section: Comparison With Other Regions and Countriessupporting
confidence: 89%
“…Also, studies performed in Brazil [7][25] [55] showed high concentrations of a-thujone, 1,8-cineole, and camphor as the principal components, very similar to the levels we found, although they found no manool or viridiflorol.…”
Section: Comparison With Other Regions and Countriessupporting
confidence: 89%
“…A previous studies have revealed -thujone, 1,8-cineole, β-pinene, β-thujone, camphor and borneol to be the major constituents of the sage essential oil [1,2,3,4,5,6,8,11,14,15,16,18,19,20,21]. Different chemotypes have been described for sage:…”
Section: Introductionmentioning
confidence: 99%
“…Besides is also evidently rich in essential oils and phenolic acids [22]. Salvia essential oil is also effective against several bacteria [23]. The first dominant constituents are cis-thujone, 1,8-cineole, camphor, trans-thujone, α-humulene and linalool [24].…”
Section: Essential Oilsmentioning
confidence: 99%